Comprehensive Analysis of Business Models of AgriTechs in Uzbekistan - Kumari, Jyothi; Govind, Ajit; Akramkhanov, Akmal (International Center for Agricultural Research in the Dry Areas, 2024)
Agriculture is a pivotal sector in Uzbekistan, employing 26.8% of the workforce and contributing 25.1% of GDP. Small-scale producers, including household farms and dehkan farmers, generate over 70% of agricultural output but use only 20% of arable land. The sector faces significant challenges such as soil degradation, water shortages, and inefficient practices. These issues are exacerbated by limited access to formal markets and financial resources, which constrains growth and productivity. To address these challenges, the Uzbek government has launched the Strategy for the Development of Agriculture (2020-2030), which aims for a 5% annual growth by 2025. The strategy focuses on improving food security, creating a favorable business climate, increasing investment, and enhancing resource management. Key measures include modernizing land management, expanding water-saving irrigation, supporting small producers, and boosting agricultural productivity. The government is dedicated to leveraging digital technologies to modernize agriculture. The Digital Uzbekistan 2030 strategy focuses on implementing projects to foster digital transformation, including investing in cutting-edge agricultural technologies. This creates opportunities for the agriTech startup community in Uzbekistan, which is currently in its early stages and grappling with funding challenges and limited internet access in rural areas. The F2R-CWANA initiative, led by ICARDA under the One CGIAR program, addresses the severe agricultural and climate-related challenges in Central and West Asia and North Africa (CWANA). The initiative aims to leverage the expertise of eight CGIAR Centers and local knowledge to deliver tailored, evidence-based solutions for climate resilience, nutrition, and agri-food systems. To support agricultural innovation, the AgriTech4Uzbekistan program was launched. This accelerator program, part of the F2R-CWANA initiative, focuses on fostering a vibrant ecosystem for agriTech start-ups in Uzbekistan. The AgriTech4Uzbekistan Innovation Challenge 2023 offered a robust support system for AgriTech start-ups. The challenge targeted innovative solutions in digital agriculture, precision farming, water management, financial services, and supply chain management to address issues like water scarcity and enhance financial access, particularly for women entrepreneurs. The AgriTech4Uzbekistan Innovation Challenge has been instrumental in highlighting a dynamic array of start-ups ready to tackle urgent agricultural and climate-tech issues. By concentrating on five pivotal areas—Digital Agriculture & Precision Farming, Capacity Building, Water Management & Irrigation Systems, Financial Services, and Supply Chain Management—these start-ups present a spectrum of innovative and impactful solutions. The challenge effectively demonstrates the sector’s potential to revolutionize agricultural practices not just within Uzbekistan, but on a global scale. The integration of advanced technologies and tailored solutions across these priority areas illustrates the transformative power of the agriTech sector. These innovations promise to enhance agricultural efficiency, sustainability, and resilience. The varied marketing strategies and funding approaches of the start-ups underscore the sector’s vibrant and adaptive nature, reflecting how these ventures are equipped to address both regional and international challenges. To enhance the effectiveness and impact of start-ups, several key recommendations are proposed: foster collaboration among start-ups in complementary fields to create integrated solutions, provide targeted support for scaling through funding and strategic partnerships, and develop tailored funding programs to address diverse needs. Additionally, encourages exploration of regional and global markets, strengthens capacity-building efforts to improve technology use, and facilitates cross-sector knowledge sharing to drive innovation. Start-ups should also optimize marketing strategies based on their target audiences, implement robust mechanisms to monitor and evaluate their impact and prioritize rigorous data protection and privacy practices.